2020
DOI: 10.1038/s41598-019-56355-5
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a new predictive model to improve risk stratification in bronchopulmonary dysplasia

Abstract: We need a better risk stratification system for the increasing number of survivors of extreme prematurity suffering the most severe forms of bronchopulmonary dysplasia (BPD). However, there is still a paucity of studies providing scientific evidence to guide future updates of BPD severity definitions. Our goal was to validate a new predictive model for BPD severity that incorporates respiratory assessments beyond 36 weeks postmenstrual age (PMA). We hypothesized that this approach improves BPD risk assessment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…In support of this, in this study, we found that oxygen supplementation was disproportionally greater among extremely preterm infants, particularly in those with subsequent respiratory hospitalizations. This agrees with prior studies reporting that oxygen supplementation >120 days is an independent predictor of prolonged hospitalizations or readmissions for lower respiratory tract infections in premature infants [ 17 , 26 ]. We believe that premature infants born ≤27 weeks GA have a much higher risk of long-term complications and respiratory hospitalizations during the first two years of life due to additional pathogenic mechanisms, including abnormal development of the lungs and additional components of the respiratory system (e.g., autonomic and ventilatory control), as well as iatrogenic factors during prolonged NICU hospitalizations.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In support of this, in this study, we found that oxygen supplementation was disproportionally greater among extremely preterm infants, particularly in those with subsequent respiratory hospitalizations. This agrees with prior studies reporting that oxygen supplementation >120 days is an independent predictor of prolonged hospitalizations or readmissions for lower respiratory tract infections in premature infants [ 17 , 26 ]. We believe that premature infants born ≤27 weeks GA have a much higher risk of long-term complications and respiratory hospitalizations during the first two years of life due to additional pathogenic mechanisms, including abnormal development of the lungs and additional components of the respiratory system (e.g., autonomic and ventilatory control), as well as iatrogenic factors during prolonged NICU hospitalizations.…”
Section: Discussionsupporting
confidence: 93%
“…The degree to which improvements in respiratory outcomes after NICU discharge can be achieved for most premature infants is unclear, especially in the post-surfactant era. Our team and others [ 8 , 12 - 17 ] have shown that despite surviving early respiratory complications, infants born severely premature (≤32 weeks GA) have very high rates of respiratory hospitalizations after NICU discharge. It is possible that extremely premature babies born at the limit of the viability of lung development have an even greater risk of respiratory morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few decades, many predictive models for BPD have been developed using clinical variables, such as GA, BW, sex, IUGR, MV time, and HsPDA ( 25 , 26 ). As expected, smaller GA, male sex, IUGR, MV time in the first week of life and type of respiratory support on the 7th day after birth were important predictors of moderate-to-severe BPD/death, and patients with HsPDA were more likely to develop moderate-to-severe BPD.…”
Section: Discussionmentioning
confidence: 99%
“…Most predictive models include several BPD risk factors, such as birth weight, GA, chorioamnionitis, preeclampsia, respiratory parameters, etc. ( Ding et al, 2020 ; Valenzuela-Stutman et al, 2019 ; Nino et al, 2020 ). These known risk factors increase neonatologists’ awareness of the potential risk of BPD in selected patients but are still not able to universally identify patients with a high risk of developing moderate to severe BPD and tend to overestimate this risk.…”
Section: Resultsmentioning
confidence: 99%